#1**+4 **

3x + 3y = 9

5x - 8y = -9

Multiply the top equation through by -5/3.

3(-5/3)x + 3(-5/3)y = 9(-5/3)

-5x - 5y = -15

Now line this up with the second equation and add straight down.

-5x - 5y = -15

+ __ 5x - 8y = -9__

0x - 13y = -24

-13y = -24

y = -24/-13

**y = 24/13**

Now substitute this value for y into either equation to find x.

3x + 3(24/13) = 9

3x = 9 - 72/13

3x = 45/13

**x = 15/13**

hectictar
May 7, 2017

#1**+4 **

Best Answer

3x + 3y = 9

5x - 8y = -9

Multiply the top equation through by -5/3.

3(-5/3)x + 3(-5/3)y = 9(-5/3)

-5x - 5y = -15

Now line this up with the second equation and add straight down.

-5x - 5y = -15

+ __ 5x - 8y = -9__

0x - 13y = -24

-13y = -24

y = -24/-13

**y = 24/13**

Now substitute this value for y into either equation to find x.

3x + 3(24/13) = 9

3x = 9 - 72/13

3x = 45/13

**x = 15/13**

hectictar
May 7, 2017